Explaining Local Manufacturing Growth in Chile : The Advantages of Sectoral Diversity - Almeida, Rita; Fernandes, Ana M. (2012)
This paper investigates whether the agglomeration of economic activity in regional clusters affects long-run manufacturing total factor productivity growth in an emerging market context. It explores a large firm-level panel dataset for Chile during a period characterized by high growth rates and rising regional income inequality (1992-2004). The findings are clear-cut. Locations with greater concentration of a particular sector did not experience faster growth in total factor productivity during this period. Rather, local sector diversity was associated with higher long-run growth in total factor productivity. However, there is no evidence that the diversity effect was driven by the local interaction with a set of suppliers and/or clients. The authors interpret this as evidence that agglomeration economies are driven by other factors, such as the sharing of access to specialized inputs not provided solely by a single sector, such as skills or financing.